-6(9-5х)=9х+9                       -3(1+4х)=-4х-5                     

-6(9-5х)=9х+9                       -3(1+4х)=-4х-5                     
Гость
Ответ(ы) на вопрос:
Гость
-6(9-5х)=9х+9 -54+30х=9х+9 30х-9х=9+54 21х=63 х=3 -------- -3(1+4х)=-4х-5 -3-12х=-4х-5 -12х+4х=-5+3 -8х=-2 х=0.25
Гость
1) -6(9-5х)=9х+9,       -54 +30х=9х+9,              30х - 9х = 9 + 54                21х = 63                х= 63 : 21                х=3 2)  -3(1+4х)=-4х-5,      -3 - 12 х = - 4х - 5,      -12 х + 4 х = - 5 + 3         - 8 х = - 2          х = (-2) : (-8)        х = 1/4      х= 0,25  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы